Broadband chiral hybrid plasmon modes on nanofingernail substrates. Issue 6 (29th January 2020) - Librizzi, Paulina; Biswas, Aneek; Chang, Roger; Kong, Xiang-Tian; Moocarme, Matthew; Ahuja, Gaurav; Kretzschmar, Ilona; Vuong, Luat T.
Abstract : Inverted glancing angle deposition produces closely-spaced, out-of-plane structures around apertures. These nanofingernails exhibit chiral hybrid multi-polar modes, tilted Poynting vector power flows, and hotspots that depend on illuminating circular-polarization handedness. Abstract : There is significant interest in the utility of asymmetric nanoaperture arrays as substrates for the surface-enhanced detection, fluorescence, and imaging of individual molecules. This work introduces obliquely-cut, out-of-plane, coaxial layered structures on an aperture edge. We refer to these structures as nanofingernails, which emphasizes their curved, oblique, and out-of-plane features. Broadband coupling into chiral hybrid plasmon modes and helicity-dependent near-field scattering without circular dichroism are demonstrated. The unusually-broadband, multipolar modes of nanofingernail micropore structures exhibit phase retardation effects that may be useful for achieving spatial overlap at different frequencies. The nanofingernail geometry shows new potential for simultaneous polarization-enhanced hyperspectral imaging on apertured, plasmonic surfaces.